Perinatal findings and outcomes in a very rare congenital bulky retroperitoneal Ewing sarcoma: A case report - Irene Aracil Moreno; Sylvia Caballero Martín; Ana Ceballos Medina; Francisco Javier Díaz-Crespo; Samuel Navarro Fos; Virginia Ortega Abad; Juan A de León-Luis; Cristina Mata Fernández (Elsevier, 2021)
Congenital Ewing Sarcoma is extremely rare, with a poor prognosis despite early detection and intensive treatment. The Ewing Sarcoma family of tumors (ESFT) is a group of undifferentiated small round cell sarcomas, that includes Ewing sarcoma (ES) and peripheral primitive neuroectodermal tumor (pPNET), and are defined by translocations that result in the fusion of the EWS gene and a gene of the ETS family of transcription factors, EWS-FLI being the most frequent (Wang et al., 2007) [1]. While ES is mainly a primitive bone sarcoma of children or adolescents, up to 15-20% of cases appear in soft tissues, chest wall or visceral sites, and 2.6% of cases occur in patients younger than three years (Akçalı et al., 2017) [2]. Neonatal cases are very rare, and we present a male newborn, with a bulky abdominal mass detected on a routine prenatal ultrasound scan (US).